(untitled) (Journal of Oriental Studies, 2016)
In this article we stopped only on some questions of developments of the Uigur language in the conditions of intensive influence on it Chinese and first of all lexicon and a terkminologiya of the last. It is clear only that influence of Chinese on Uigur and also on languages of other non chinese will accept the increasing scales.